Introductory address - Dodd, William H. (Statistical and Social Inquiry Society of Ireland, 1896)
In the address which I had the honour to deliver as President of this society, at the opening of the last session, I took occasion to review the history and work of the society during the period, nearly half a century, in which it had been in existence. In his second address the President is expected to confine himself to general observations upon the topics that seem to him to be worthy of the attention of the society at the time. I gladly adhere to the custom. My main duty to-night is to listen not to speak.
Read Tuesday, 28th January, 1896
Keywords: Ireland, 19th century; Social change; 314.15